2019
DOI: 10.1038/s41422-019-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

A complex structure of arrestin-2 bound to a G protein-coupled receptor

Abstract: Arrestins comprise a family of signal regulators of G-protein-coupled receptors (GPCRs), which include arrestins 1 to 4. While arrestins 1 and 4 are visual arrestins dedicated to rhodopsin, arrestins 2 and 3 (Arr2 and Arr3) are β-arrestins known to regulate many nonvisual GPCRs. The dynamic and promiscuous coupling of Arr2 to nonvisual GPCRs has posed technical challenges to tackle the basis of arrestin binding to GPCRs. Here we report the structure of Arr2 in complex with neurotensin receptor 1 (NTSR1), which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
216
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(269 citation statements)
references
References 46 publications
17
216
0
Order By: Relevance
“…Nevertheless, it is tempting to hypothesize that other residue combinations bias arrestin-mediated signaling in this system towards different effectors (7,8). This is consistent with reported different shapes of the arrestin-receptor complex (68)(69)(70). We also identified different effects of G protein on this process, with Gs enhancing ERK1/2 but not Src activation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, it is tempting to hypothesize that other residue combinations bias arrestin-mediated signaling in this system towards different effectors (7,8). This is consistent with reported different shapes of the arrestin-receptor complex (68)(69)(70). We also identified different effects of G protein on this process, with Gs enhancing ERK1/2 but not Src activation.…”
Section: Discussionsupporting
confidence: 87%
“…Crystal structures of the receptor-arrestin complexes indeed reveal that arrestin binds to both the phosphorylated elements in the C-terminus and the pocket unique to active receptor (the main G protein binding site) (67)(68)(69)(70). While phosphorylation commonly reduces G protein coupling (71)(72)(73), in some cases it changes the G protein subtype that couples to receptor (50,74).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, GPCR‐arrestin complexes are highly dynamic and the biophysical determination of their structure is technically very challenging. To date, only a few 3D structures of arrestin–GPCR complexes have been solved: the crystal structure of the rhodopsin (Rho)‐bound arr1 (Kang et al , 2015; Zhou et al , 2017), and the three very recent cryo‐electron microscopy (cryo‐EM) structures of βarr1 in complex with the class B NTS 1 R (Yin et al , 2019; Huang et al , 2020), the muscarinic acetylcholine‐2‐receptor (M 2 R) (Staus et al , 2020), and the β 1 ‐adrenoceptor (β 1 ‐AR) (Lee et al , 2020). The β 1 ‐AR belongs to class A arrestin binders (Shiina et al , 2000, Eichel et al , 2016), whereas contradictory findings have been reported for the M 2 R (Gurevich et al , 1995, Jones et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In several structures of the receptor-arrestin complexes, the polar core arginine does not interact with the receptor-attached phosphates (Huang et al, 2020;Kang, Zhou, & Gao, 2015;Staus et al, 2020;Yin et al, 2019;Zhou et al, 2017). Instead, a lysine (Lys301 in mouse arrestin-1, homologous to Lys300 in bovine arrestin-1, Lys294 in arrestin-2, and Lys295 in arrestin-3) on the "lariat loop" (Hirsch et al, 1999) was found in direct contact with one of the phosphates in the phosphorylated receptors.…”
mentioning
confidence: 99%